"THE SILLY PICTURES DISAPPEAR": EPHEMERAL SOCIAL MEDIA AS BOUNDARY PLAY - Shklovski, Irina; Hervik, Simon Bruun (AoIR Selected Papers of Internet Research, 2015)
In contrast to the "total recall" and "save everything" ethos of many digital pioneers, recent popularity of applications such as Snapchat that offer deletion of captured and shared media by default from both the sender and the receiver devices suggests that ephemerality of digital content is important. However, little is known about what role ephemerality plays in the use of communication media. Snapchat is a mobile phone application that allows its users to take, easily modify and share mobile photos. The application provides a significant level of control to senders allowing them to set how long the receiver can see an image, before it self-destructs. The system, however, can be relatively easily circumvented through the use of screenshots or dedicated applications designed to save Snapchat content. In this paper we present a study of college student use of Snapchat based on observations, informal conversations, and focus group interviews. We discuss the reasons our participants propose for using Snapchat and its role in student social practice. We find that our participants use Snapchat alongside rather than instead of Facebook and Instagram and argue that much of Snapchat use can be interpreted as forms of relational boundary play precisely because of expected deletion by default.